Root branching: mechanisms, robustness, and plasticity - Ghosh Dastidar, Mouli; Jouannet, Virginie; Maizel, Alexis (WIREs. Developmental Biology, 2012)
Plants are sessile organisms that must efficiently exploit their habitat for water and nutrients. The degree of root branching impacts the efficiency of water uptake, acquisition of nutrients, and anchorage. The root system of plants is a dynamic structure whose architecture is determined by modulation of primary root growth and root branching. This plasticity relies on the continuous integration of environmental inputs and endogenous developmental programs controlling root branching. This review focuses on the cellular and molecular mechanisms involved in the regulation of lateral root distribution, initiation, and organogenesis with the main focus on the root system of Arabidopsisthaliana. We also examine the mechanisms linking environmental changes to the developmental pathways controlling root branching. Recent progress that emphasizes the parallels to the formation of root branches in other species is discussed. WIREs Dev Biol 2012, 1:329-343. doi: 10.1002/wdev.17 For further resources related to this article, please visit the WIREs website.